2015
DOI: 10.4238/2015.march.20.13
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution melting curve analysis of the ADSL and LPL genes and their correlation with meat quality and blood parameters in chickens

Abstract: ABSTRACT. Adenylosuccinate lyase (ADSL) and lipoprotein lipase (LPL) are key enzymes in the metabolism of inosine monophosphate (IMP) and fat mass, which are important factors in meat quality evaluation. In this study, we selected 50 hens from the ISA B-line layers and Guangxi Yellow chickens, slaughtered the chickens at 120 days old, and analyzed polymorphisms in the ADSL and LPL genes using the highresolution melting curve method. Blood lipid parameters, intramuscular fat (IMF), and IMP content were higher (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
(13 reference statements)
0
14
0
Order By: Relevance
“…Total of 33 (between breeds) and seven (between ages) DEGs were associated with IMF deposition (Supplementary Table 3). There were 24 DEGs down-regulated in WC chicken, including several well-known candidate genes for lipid metabolism, such as ABCA1 (Santamarina-Fojo et al, 2001), ACACB (Xu et al, 2014), CPT1A (Akkaoui et al, 2009), LPL (Claire et al, 2013; Zhang X. D. et al, 2015), and SLC27A1 (Sebastian et al, 2009; Guitart et al, 2014), of which SLC27A1 was also more down-regulated in WRR.D180.B than in WRR.D120.B. In other words, SLC27A1 were generally lower expressed in the higher IMF muscles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total of 33 (between breeds) and seven (between ages) DEGs were associated with IMF deposition (Supplementary Table 3). There were 24 DEGs down-regulated in WC chicken, including several well-known candidate genes for lipid metabolism, such as ABCA1 (Santamarina-Fojo et al, 2001), ACACB (Xu et al, 2014), CPT1A (Akkaoui et al, 2009), LPL (Claire et al, 2013; Zhang X. D. et al, 2015), and SLC27A1 (Sebastian et al, 2009; Guitart et al, 2014), of which SLC27A1 was also more down-regulated in WRR.D180.B than in WRR.D120.B. In other words, SLC27A1 were generally lower expressed in the higher IMF muscles.…”
Section: Resultsmentioning
confidence: 99%
“…LPL (Lipoprotein lipase) has the dual functions of triglyceride hydrolase and lipoprotein uptake (Gotoda et al, 1989; Goldberg, 1996). LPL is an important candidate gene for chicken lipid metabolism, and the mRNA level and enzymatic activity of LPL was negatively correlated with IMF contents (Claire et al, 2013; Zhang X. D. et al, 2015). SLC27A1 is involved in translocation of long-chain fatty acids (LFCAs) across the plasma membrane and subsequently lipid metabolism in skeletal muscle (García-Martínez et al, 2005; Sebastian et al, 2009; Holloway et al, 2011; Guitart et al, 2014), heart (Chiu et al, 2005), 3T3-L1 cell (Lobo et al, 2007), and 293 cell (Hatch et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, previous studies also suggested that LPL in abdominal adipose tissue plays a crucial role in fat accumulation in broiler chickens (Sato et al, 1999). Using high-resolution melting curves, Zhang et al (2015) showed that ADSL (adenylosuccinate lyase) and LPL gene mutations were correlated with meat quality differences in GXSH chickens and ISA B-line layers. However, knowledge of the developmental expression patterns of LPL mRNA, LPL enzyme activity, and the relationship of each with IMF contents in GXSH chicken is limited.…”
Section: Introductionmentioning
confidence: 90%
“…Up till now, breed-related differences in the capacity of lipid accumulation have been documented in pig ( Wood et al 2004a ; Tyra et al 2013 ), cattle ( Gotoh et al 2009 ), sheep ( Qiao et al 2008 ), and chicken ( Wang et al 2016 ). A number of single nucleotide polymorphisms (SNPs) significantly associated with the IMF trait of meat have been detected in functional genes involved in the lipid metabolism, which include the FABP (fatty acid-binding protein) (pig, Cho et al 2011 ; beef cattle, Avilés et al 2013 ), LPL (lipoprotein lipase) (chicken, Zhang et al 2015 ), and DAGT1 (diacylglycerol acyltransferase) (cattle, Wu et al 2012 ). Meanwhile, effects of genetic variants on FA composition were also demonstrated ( Taniguchi et al 2004 ; Wood et al 2008 ).…”
mentioning
confidence: 99%